Metaheuristics for strain optimization using transcriptional information enriched metabolic models - Vilaça, Paulo (2010)
Publicado em "Evolutionary computation, machine learning and data mining in bioinformatics : 8th European Conference, EvoBIO 2010...", ISBN 978-3-642-12210-1